Trade Linkages and International Business Cycle Comovement : Evidence from Korean Industry Data - Lee, Dongyeol (IMF Working Papers; Working Paper ;, 2019)
Through the 2000s, Korea's export and import linkages to advanced and emerging markets increased significantly. At the same time, the correlation of output growth between Korea and these economies rose. This paper investigates the nature of the link between trade linkages and the comovement of international business cycles (BC) using Korean industry-level domestic and international input-output data. The results suggest that, at the industry-level, higher export linkages lead to a larger positive GDP growth comovement, while higher import linkages lead to higher negative employment growth comovement. Furthermore, the decomposition of aggregate BC comovement shows that the increase in trade with China has contributed the most to aggregate BC comovement, while the impact of trade linkages on BC comovement is propagated domestically via vertical linkages. These findings suggest that the Korean economy can be significantly affected by a few countries that are highly linked through trade to Korea and/or a few industries that are highly interconnected to other industries.